SYNERGETIC OF THE TECTONIC FLOW OF ROCKS IN BREAK ZONES - LUKIIENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Tectonic flow of rocks in break zones is considered as self-organizing process which is guided by the synergetic laws. The basic features of this process are determined. The power factors and mechanisms of this process are determined.